Role of antifungal combinations in difficult to treat candida infections - Vitale, Roxana Gabriela (2021)
Candida infections are varied and, depending on the immune status of the patient, a life-threatening form may develop. C. albicans is the most prevalent species isolated, however, a significant shift towards other Candida species has been noted. Monotherapy is frequently indicated, but the patient’s evolution is not always favorable. Drug combinations are a suitable option in specific situations. The aim of this review is to address this problem and to discuss the role of drug combinations in difficult to treat Candida infections. A search for eligible studies in PubMed and Google Scholar databases was performed. An analysis of the data was carried out to define in which cases a combination therapy is the most appropriate. Combination therapy may be used for refractory candidiasis, endocarditis, meningitis, eye infections and osteomyelitis, among others. The role of the drug combination would be to increase efficacy, reduce toxicity and improve the prognosis of the patient in infections that are difficult to treat. More clinical studies and reporting of cases in which drug combinations are used are needed in order to have more data that support the use of this therapeutic strategy.